FORMULASI SEDIAAN LOTION ANTIOKSIDAN DARI EKSTRAK ETANOL DAUN RAMBUTAN NEPHELIUM LAPPACEUM LINN - Noorma Yahni; Nur Mahdi; Ani Agustina (LPPM - Universitas Muhammadiyah Banjarmasin, 2022)
from exposure to foreign substances and sunlight. Several factors cause skin damage, one of wich is radiation. Rambutan leaves contain flavonoids wich are useful as antioxidant, so they can be used and formulated as antioxidant lotions. The next experiment aims to determine the antioxidant activity of the ethanol extract of rambutan leaves (Nephelium Lappaceum Linn) using the PPDH method with concentrations of 10ppm, 20ppm, 30ppm, 40ppm, and 50ppm to obtain an IC50 of 15,505ppm (very strong). The formulation was made with four concentrations of F0 (basis), F1 (0,0016 gr), F2 (0,002 gr) and F3 (0,0024 gr) To get a stable lotion, physical stability evaluation was carrier out by means of organoleptic, homogeneity, pH, dispersibility, adheasone, viscosity testThe result of the physical stability test of the lotion preparation met the criteria for a good lotion preparation on organoleptic, homogeneity, pH and dispersibility, the adhesion test did not meet the criteria for a good lotion